Analisis Yuridis Kepemilikan Hak Atas Tanah Terdaftar Atas Nama Anak Yang Bersumber Dari Nominee Akta (Studi Putusan Nomor: 433K/PDT/2016) - Muhammad Takkas Siregar (Recital Review, 2020)
Nominee Arrangement drafted by a Notary has quite wide range of usage because it contains authority. Nominee is principally an agreement that is not assertively specifically regulated, but in practice, it is used as an agreement with name borrowing which existence frequently brings negative impacts and financial loss to all parties if its deed is proceeded. The objective of this research was to analyze the legal regulations related to notarial deed drafting categorized into deed of nomination, the legal status of the land title registered with the name of a child mentioned in a nominee deed, and the Verdict of the Supreme Court Number 433K/Pdt/2016. Normative juridical research method is employed with descriptive analysis. The data are collected through library study. The research problems are about the land title ownership sourced from nominee or name borrowing. The legal regulations on notarial deeds that are categorized into deed of nomination causes many legal problems in practice; thus, the practice of nominee arrangement has to be made with a supporting agreement to build legal relationship among all parties, that the legal smuggling seems legitimate and has legal ground. The results demonstrate that the usage of nominee concept in land ownership is aimed at protecting the confidentiality of the true owner’s name and identity from public and government. The legal status of deed of nomination is not specifically regulated, but the Law on Capital Market and Law on Limited Liability Companies stipulate regulations on nominee. The analysis result of this verdict is that the judges should be more conscientious in analyzing, deciding, and pronouncing the verdict by involving competent experts; it can be made guidance to make decision. The ruling issued by a court reflects a just legal protection for all disputed parties in Indonesia.